Draft Sixth Five Year Plan 1978-83 Manipur Department of Animal Husbandry - Planning Commission (Planning Commission, 1978)
In the earlier plans the allotment was very merge and in the fought-five-year plan an allocation of Rs. 54.00 lakhs has been made. As such no significant contribution could be produced out of the schemes taken up in the Deptt. of Vety. & A.H. Manipur. However in the 5th Plan an allocation of Rs.240.00 lakhs which was further reduced to Rs.199.00 lakhs has been made and the Department moved ahead in the sphere of livestock production and Animal Health Coverage Programme.
Department of Veterinary and Animal Husbandry: Diary Manipur